Pleiotropic effects of vitamin D3 on CD4+ T lymphocytes mediated by human periodontal ligament cells and inflammatory environment. (13th April 2020) - Behm, Christian; Blufstein, Alice; Gahn, Johannes; Kubin, Barbara; Moritz, Andreas; Rausch‐Fan, Xiaohui; Andrukhov, Oleh
Abstract: Aims: Both, vitamin D3 and human periodontal ligament cells (hPDLCs) possess immunosuppressive properties, but their combined effect on immune cells has never been investigated. Here, we analysed the impact of vitamin D3 on the immunosuppressive properties of hPDLCs towards CD4 + T lymphocytes. Material and Methods: Allogenic CD4 + T lymphocytes were activated by phytohemagglutinin either in monoculture or co‐culture with hPDLCs, in the presence or absence of IFN‐γ and 1, 25(OH)2 D3 . After 5 days, CD4 + T‐lymphocyte proliferation, CD4 + CD25 + FoxP3 + regulatory T lymphocytes (Tregs ) proportion and IL‐10, TGF‐β1 and IL‐17A production were analysed. Results: In monoculture, 1, 25(OH)2 D3 suppressed CD4 + T‐lymphocyte proliferation, increased the percentage of CD4 + FoxP3 + CD25 + FoxP3 + Tregs and enhanced IL‐10 and TGF‐β1 production. In the presence of IFN‐γ treated hPDLCs, 1, 25(OH)2 D3 significantly increased CD4 + T‐lymphocyte proliferation and decreased the percentage of CD4 + CD25 + FoxP3 + Tregs . IL‐10 and IL‐17A expression was significantly diminished by 1, 25(OH)2 D3, whereas TGF‐β1 was slightly increased. The effects of 1, 25(OH)2 D3 in co‐culture were reversed by inhibition of indoleamine‐2, 3‐dioxygenase‐1, prostaglandin‐endoperoxide synthase and programmed cell death 1 ligand 1. 1, 25(OH)2 D3 also suppressed the expression of these proteins in hPDLCs. Conclusion: Effects of vitamin D3 on CD4 + T lymphocyte are modified by hPDLCs depending on the microenvironment.